2017
DOI: 10.5664/jcsm.6622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the New Generation of Devices for Positional Therapy for Patients With Positional Obstructive Sleep Apnea: A Systematic Review of the Literature and Meta-Analysis

Abstract: Study Objectives:In approximately 56% to 75% of patients with obstructive sleep apnea (OSA), the frequency and duration of apneas are influenced by body position. This is referred to as position-dependent OSA or POSA. Patients with POSA can be treated with a small device attached to either the neck or chest. These devices-a new generation of devices for positional therapy (PT)-provide a subtle vibrating stimulus that prevents patients adopting the supine position. The objectives of this study were to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 62 publications
0
44
0
4
Order By: Relevance
“…P values compare data between responders and non-responders. by Ravesloot et al 34 In addition, Barnes et al 35 reviewed the positional modification techniques. In this study, the SPT was used in the routine clinical practice for the treatment of POSA, meaning that any patient in whom POSA was diagnosed was offered to try treatment with the SPT.…”
Section: Discussionmentioning
confidence: 99%
“…P values compare data between responders and non-responders. by Ravesloot et al 34 In addition, Barnes et al 35 reviewed the positional modification techniques. In this study, the SPT was used in the routine clinical practice for the treatment of POSA, meaning that any patient in whom POSA was diagnosed was offered to try treatment with the SPT.…”
Section: Discussionmentioning
confidence: 99%
“…22 POSA is increasingly important to recognize as advances in the delivery of position therapy using vibrotactile feedback have contributed to improved outcomes, and long-term compliance compared to traditional techniques (eg, tennis ball t-shirts, restrictive pillows, or padding). 19,[23][24][25] The characterization of POSA has also evolved, improving the likelihood that clinically important reductions in overall OSA severity will be achieved if supine sleep is avoided. 20 Unfortunately, if split night PSG or Type III studies without sleep position monitoring capability are used in the assessment of OSA, clinicians cannot routinely identify which patients might benefit from position therapy alone or in combination with oral appliance therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly positional therapy (lateral sleep) is helpful in these patients to resist the collapse and improve apnea [57] . Study revealed that positional therapy in positional OSA patients reshape the velopharyngeal airway, decreased its collapsibility during Muller maneuver, reduction of snoring intensity, and increase of oxygen saturation [58] . Further, the majority of non-positional OSA patients after palatal surgery turn out to be positional OSA patients [59] .…”
Section: Postoperative Integrated Treatmentmentioning
confidence: 97%